Exploring the Phenomenon of Presence in an Online Educational Environment Through the Lived Experiences of Graduate Nursing Faculty - (:unkn) unknown (My University, 2014)
In this dissertation, the phenomenon of presence in an online educational environment is explored through the lived experiences of graduate nursing faculty who teach online. Greater understanding of the phenomenon of presence in online educational environments may lead to better learner-instructor relationships, higher levels of inquiry and critical thinking on the part of faculty and students, and ultimately better student outcomes. Utilizing principles of Hermeneutic Phenomenology and deductive inquiry, and based on the learner-centric Being There for the Online Learner Model, the author conducted in-depth interviews with a purposive sample of 13 graduate nursing faculty members who teach online at a major university in the northeast United States. The author also reviewed supporting documents pertaining to institutional structure, faculty development, the institution's learning management system, and online faculty job descriptions. Interview data were analyzed thematically, using the mixed-methods software Dedoose. Results of the study revealed four ways in which graduate nursing faculty experience the sense of presence (i.e., The Modes of Presence derived from the Being There for the Online Learner Model): Realism, Involvement, Immersion, and the Willing Suspension of Disbelief. Two broad themes, Being there and Being Together were also identified. Being There is the sensation that occurs when graduate nursing faculty feel or perceive they are physically in another location when teaching online. Being Together is the sensation that graduate nursing faculty are physically in the same space with others (i.e., their students), when they are actually separated by distance. In both cases, this is for varying lengths of time, and with varying frequency. The study identified three main conclusions: not all participants experience the sense of presence in the same way; Being There may also include the sensation of "Coming Here"; and, The Illusion of Nonmediation, as described in the Model, should be considered as a fifth Mode of Presence. Based upon these conclusions, I present implications for nursing education science and provide recommendations for creating the sense of presence in online educational environments.
Keywords: Being There for the Online Learner Model; Distance Education; Graduate Nurisng Faculty; Presence